Proteome Profiling of Wheat Shoots from Different Cultivars - Vu, Lam Dai; Verstraeten, Inge; Stes, Elisabeth; Van Bel, Michiel; Coppens, Frederik; Gevaert, Kris; De Smet, Ive (Frontiers in Plant Science, 2017)
Wheat is a cereal grain and one of the world’s major food crops. Recent advances in wheat genome sequencing are by now facilitating its genomic and proteomic analyses. However, little is known about possible difference in total protein levels of hexaploid versus tetraploid wheat cultivars, and also knowledge on phosphorylated wheat proteins is still limited. Here, we performed a detailed analysis of the proteome of seedling leaves from two hexaploid wheat cultivars (T. aestivum L. Pavon 76 and USU-Apogee) and a tetraploid wheat (Triticum turgidum ssp. durum cv. Senatore Cappelli). Our shotgun proteomics data revealed that while we observed some significant differences, overall a high similarity between hexaploid and tetraploid varieties with respect to protein abundance was observed. In addition, already at the seedling stage, a small set of proteins were differential between the small (USU-Apogee) and larger hexaploid wheat cultivars (Pavon 76), which could potentially act as growth predictors. Finally, the phosphosites identified in this study can be retrieved from the in-house developed plant PTM-Viewer (bioinformatics.psb.ugent.be/webtools/ptm_viewer/), making this the first searchable repository for phosphorylated wheat proteins. This paves the way for further in depth, quantitative (phospho)proteome-wide differential analyses upon a specific trigger or environmental change.